Encapsulation of DHA oil with heat-denatured whey protein in Pickering emulsion improves its bioaccessibility. (December 2022) - Wang, Jun; Ossemond, Jordane; Jardin, Julien; Briard-Bion, Valérie; Henry, Gwenaële; Le Gouar, Yann; Ménard, Olivia; Lê, Sébastien; Madadlou, Ashkan; Dupont, Didier; Pédrono, Frédérique
Graphical abstract: Highlights: DHA oil was encapsulated with whey proteins as Pickering emulsion. Such an encapsulation generates smaller lipid droplets in omelet used as food matrix. Thus, it increases the bioaccessibility of the DHA oil. Consequently, intestinal hydrolysis of DHA oil with pancreatic lipase was promoted. DHA is ultimately released as free fatty acid abundantly and earlier during digestion. Abstract: This study compared the bioaccessibility of docosahexaenoic acid (DHA) provided encapsulated or unencapsulated within a food matrix. DHA oil was composed of DHA-enriched triacylglycerols prepared as Pickering emulsion by encapsulation with heat-denatured whey protein isolate particles and then incorporated into homogenized liquid egg to get omelets. The effect of encapsulation was analyzed by using a static in vitro digestion model of the adult, which digestive fluid enzymes have also been characterized by proteomics. First, the size of lipid droplets was shown to be smaller and uniformly dispersed in omelets with encapsulated-DHA oil compared to non-encapsulated-DHA oil. Distribution of droplets was more regular with encapsulated-DHA oil as well. As a consequence, we showed that encapsulating DHA oil promoted the hydrolysis by pancreatic lipase during the intestinal phase. A larger proportion of DHA enriched-triacylglycerols was hydrolyzed after two hours of digestion, leading to a greater release in free DHA. Thus, only 32% of DHA remained esterified in the triacylglycerols with encapsulated-DHA oil, compared to 43% with non-encapsulated-DHA oil. The DHA in free form ultimately represented 52% of the total DHA with encapsulated-DHA oil, compared to 40% with non-encapsulated-DHA oil. Finally, our results showed that as much DHA was released after one hour of intestinal digestion when the DHA oil was encapsulated as after two hours when the DHA oil was not encapsulated. Therefore, DHA bioaccessibility was significantly improved by encapsulation of DHA oil in omelets.